Structural study on the interactions of oxaliplatin and linear DNA. Issue 6 (8th July 2016) - Zou, Yongpeng; Biao, Linhai; Xu, Fengjie; Liu, Ruisi; Liu, Zhiguo; Fu, Yujie
Summary: Damage to cellular DNA is believed to determine the cytotoxicity of oxaliplatin. However, high resolution structures formed by oxaliplatin and different linear DNA remain unclear. This study characterized, the key structures of different linear DNA in the platination process by UV absorption spectra and atomic force microscopy (AFM). Bathochromic shift and hyperchromicity in UV spectra after addition of oxaliplatin revealed that it can disrupt base stacking of DNA in the platination process. AFM results of different linear DNA indicated that, the platination process can induce DNA change from an extended conformation to the network structure with many kinks and finally to the compact particles, or toroids with increasing the incubation time. All AFM results confirmed that, platination of different linear DNA by oxaliplatin is a time depended process. The present AFM results provide, structural evidence about the interactions between oxaliplatin and different linear DNA containing multiple targets. SCANNING 38:880–888, 2016. © 2016 Wiley Periodicals, Inc.